Description of Some Methodologies for the Synthesis of 1,4-Naphthoquinone Derivatives and Examples of their Biological Activity: A Review - Loredo-Carrillo, Silvia E.; Leyva, Elisa; López-López, Lluvia I.; Navarro-Tovar, Gabriela; de Loera, Denisse; Vega-Rodríguez, Sarai (Current Organic Chemistry, 2024)
An alternative to finding new drugs for the treatment of various diseases is the chemical modification of the structure of compounds of natural origin. Among them, naphthoquinones are very interesting candidates, as they are antibacterial, antifungal, antiparasitic, and anticancer agents. Naphthoquinones are redox compounds that can accept one or two electrons, generating reactive oxygen species in the cell and producing cell apoptosis. Naphthoquinones are unsaturated compounds containing a dicarbonyl sequence in the para position, which is highly reactive. Several studies of the chemical modification of naphthoquinones, either of natural origin (such as lapachol or juglone) or synthetic origin, have demonstrated the great importance and versatility of this type of compound. Polyhydroxylated derivatives, amino, thioethers, and conjugated heterosystems (indole or pyrrole groups) have been synthesized. Depending on the type of derivative, their specific use against certain types of microorganisms or cancer cell lines has been demonstrated.
Keywords: antimicrobial compounds